Case report: Difference in outcomes between two cases of Hailey-Hailey disease treated with apremilast - Yamaga, Misako; Miyauchi, Toshinari; Peh, Jin Teng; Itamoto, Sota; Mai, Yosuke; Iwata, Hiroaki; Nomura, Toshifumi; Ujiie, Hideyuki (Frontiers in Genetics, 2022)
Hailey-Hailey disease (HHD) is a rare autosomal dominant acantholytic dermatosis clinically characterized by recurrent erythematous plaques and erosions mainly on the intertriginous regions. Although HHD seriously affects quality of life, conventional treatments often fail to provide long-term relief for most patients. The effectiveness of apremilast, a phosphodiesterase-4 inhibitor, against severe HHD was first reported in 2018, and after further testing, this agent is currently expected to be established as an efficacious and safe therapeutic option. Here we report two cases of HHD treated with apremilast which showed opposite outcomes. Although the case with extremely severe symptoms showed remarkable and long-lasting improvement with apremilast used after acute treatment with oral corticosteroid, the other case, with milder symptoms treated only with apremilast, showed no improvement. Our transcriptome analysis using skin samples collected prior to apremilast administration revealed the involvement of the NF-κB signaling pathway, which is related to the responses to bacteria and other organisms. However, this pathway was more strongly activated in case 2 than in case 1, suggesting that the steroid treatment preceding apremilast may have been effective and supportive in the apremilast-responding case. One of the two cases highlights the potential of apremilast as a treatment option for HHD, but the other underlines the difficulties in managing HHD and the complexity of the disease background. The accumulation of cases and larger clinical studies are expected to precisely evaluate the safety and efficacy of apremilast, and the potential for therapies in combination with conventional treatments.